2016
DOI: 10.1002/jat.3323
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of polyacrylic acid‐coated iron oxide nanoparticles is associated with proinflammatory activation and liver toxicity

Abstract: Iron oxide nanoparticles (IONs) have physical and chemical properties that render them useful for several new biomedical applications. Still, so far, in vivo safety studies of IONs with coatings of biomedical interest are still scarce. The aim of this study, therefore, was to clarify the acute biological effects of polyacrylic acid (PAA)-coated IONs, by determining their biodistribution and their potential proinflammatory and toxic effects in CD-1 mice. The biodistribution of PAA-coated IONs in several organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The administration of polyacrylic acid-coated iron oxide nanoparticles is associated with a selective distribution in the liver that produces proinflammatory activation and liver toxicity in mice. A high accumulation of iron was also observed by macrophages phagocytosis in the periportal zone of the hepatic acinus of the liver and in the splenic red pulp of the spleen which demonstrates the specific uptake of this type of nanoparticles by the monocyte-macrophage system (101).…”
Section: As Shown Inmentioning
confidence: 72%
“…The administration of polyacrylic acid-coated iron oxide nanoparticles is associated with a selective distribution in the liver that produces proinflammatory activation and liver toxicity in mice. A high accumulation of iron was also observed by macrophages phagocytosis in the periportal zone of the hepatic acinus of the liver and in the splenic red pulp of the spleen which demonstrates the specific uptake of this type of nanoparticles by the monocyte-macrophage system (101).…”
Section: As Shown Inmentioning
confidence: 72%
“…According to existing studies, almost all of NPs have the ability to cause excessive ROS generation in affected organs, while metal or metal oxide NPs are more likely to induce oxidative stress that is evident from the increase in lipid peroxidation levels in liver, kidneys, and spleen. This effect has not been observed in heart tissue (Almeida et al, 2016;Couto et al, 2016;Teodoro et al, 2016).…”
Section: Oxidative Stressmentioning
confidence: 86%
“…Iron oxide NPs accumulate mainly in the liver and spleen, and to a lesser extent in the lungs. They tend to accumulate in liver phagocytes and elicit hepatic lipid peroxidation, showing the ability to induce oxidative stress (Couto, Freitas, Costa, & Chiste, ). High doses of silica nanorattle intravenous administration could induce liver and heart damages, which have shown to be related with the decreased activity of superoxide dismutase (SOD) (Fu et al, ).…”
Section: The Impacts Of Nps On Major Target Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of some chronic inflammatory diseases, when taking a sample requires an invasive procedure, specific in vivo tracking of monocytes will be useful to characterize different patterns of mononuclear infiltrates. In vivo studies in 8-week-old male CD-1 mice showed that after intravenous injection, poly(acrylic acid)-coated iron oxide nanoparticles (PAC-IONs) accumulated mainly in the liver and spleen, and at a lower extent in the lungs, without causing severe organ damage [39].…”
mentioning
confidence: 99%